Optimizing drip fertigation at different periods to improve yield, volatile compounds and cup quality of Arabica coffee - Li, Rongmei; Cheng, Jinhuan; Liu, Xiaogang; Wang, Zhihui; Li, Huiyong; Guo, Jinjin; Wang, Haidong; Cui, Ningbo; Zhao, Lu (Frontiers in Plant Science, 2023)
How to improve and regulate coffee bean yield and quality through split fertilization in the whole life cycle of coffee is still unclear and deserves further study. A field experiment of 5-year-old Arabica coffee trees was conducted for 2 consecutive years from 2020 to 2022. The fertilizer (750 kg ha-1 year-1, N-P2O5-K2O:20%-20%-20%) was split in three times at early flowering (FL), the berry expansion (BE), and the berry ripening (BR). Taking equal fertilization throughout the growth cycle (FL250BE250BR250) as the control check, variable fertilizations including FL150BE250BR350, FL150BE350BR250, FL250BE150BR350, FL250BE350BR150, FL350BE150BR250, and FL350BE250BR150. Leaf net photosynthetic rate (Anet), stomatal conductance (gs), transpiration rate (Tr), leaf water use efficiency (LWUE), carboxylation efficiency (CE), partial factor productivity of fertilizer (PFP), bean yield, crop water use efficiency (WUE), bean nutrients, volatile compounds and cup quality, and the correlation of nutrients with volatile compounds and cup quality was evaluated. FL350BE250BR150 had the maximum Anet and gs, followed by FL250BE350BR150. The highest dry bean yield and WUE were obtained from FL250BE350BR150, which increased by 8.86% and 8.47% compared with FL250BE250BR250 in two-year average. The ash, total sugar, fat, protein, caffeine and chlorogenic acid in FL250BE350BR150 were 6.47%, 9.48%, 3.60%, 14.02%, 4.85% and 15.42% higher than FL250BE250BR250. Cluster analysis indicated FL150BE350BR250, FL250BE350BR150, FL350BE150BR250 and FL350BE250BR150 under medium roasted degree increased pyrazines, esters, ketones and furans, FL150BE350BR250 and FL250BE350BR150 under dark roasted degree increased ketones and furans. The aroma, flavor, acidity and overall score of medium roasted coffee were higher than dark roasted coffee, while the body score of dark roasted coffee was higher than medium roasted coffee. The nutrient contents were correlated with the volatile compounds and cup quality. TOPSIS indicated that FL250BE350BR150 was the optimal fertilization mode in the xerothermic regions. The obtained optimum fertilization mode can provide a scientific basis for coffee fertilization optimization and management.